Alteração da impulsão vertical após o período competitivo em atletas de profissionais de futebol - Coledam, Diogo Henrique Constantino; Santos, Douglas dos; Santos, Julio Wilson dos [UNESP] (My University, 2010)
Change on vertical jump after competitive period in professionals soccer players. Brazilian Journal of Biomotricity, v. 4, n. 2, p. 140-147, 2010. Soccer is a sport that demands different intensities of run, with decisive actions of a match being held in maximum intensity. Vertical jump test is widely used in soccer players due to the strong relationship with speed and agility. Futhermore, there are little information about change on vertical jump after the competitive season in soccer players. The aim of this study was to analyze change on vertical jump after the competitive season in professional soccer players. Took part in this study 21 male athletes (20.82 ± 3.16 years, 72.28 ± 8.74 kg and 179.91 ± 6.14 cm) subscribers to the 4th division of the Paulista championship of 2009. The competitive season had a duration of 20 weeks, with a total of 20 official matchs done. The test used was the counter-movement vertical jump (VJ), that was performed in the first (PRE) and last (POS) training session of the competitive period. After confirmation of data normality by Kolmogorov-Smirnov, the inferential analysis of the results of VJ between PRE and POS was performed using the paired t-test, considering the significance level of 5%. There was a significant increase (p<0,05) on VJ after the competitive period (PRE=54,19±4,46 and POS=57,94±5,23). According to the results of this study, it is possible to increase the performance of VJ in professional soccer players after the competitive period of 20 weeks duration.

Alteração da impulsão vertical após o período competitivo em atletas profissionais de futebol. Brazilian Journal of Biomotricity, v. 4, n. 2, p. 140-147, 2010. O futebol é um esporte que demanda diferentes intensidades de corrida, com ações determinantes de uma partida sendo realizada em intensidade máxima. O teste de impulsão vertical é muito utilizado em atletas de futebol devido à alta correlação existente com a velocidade e agilidade. Apesar disso, existem poucas informações acerca da alteração da impulsão vertical após o período competitivo em atletas de futebol. O objetivo deste estudo foi analisar a alteração da impulsão vertical após o período competitivo em atletas profissionais de futebol. Participaram do estudo 21 atletas do gênero masculino (20,82 ± 3,16 anos, 72,28 ± 8,74 kg e 179,91 ± 6,14cm) inscritos na 4ª divisão do campeonato paulista do ano de 2009. O período competitivo teve a duração de 20 semanas, com um total de 20 jogos oficiais realizados. O teste utilizado foi o de impulsão vertical contra movimento (IV), que foi realizado na primeira (PRE) e na ultima (POS) sessão de treinamento do período competitivo. Após a confirmação da normalidade dos dados pelo teste de Kolmogorov-Smirnov, a análise inferencial dos resultados da IV entre os momentos PRE e POS foi feita através do teste-t pareado, considerando o nível de significância de 5%. Houve aumento significativo (p<0,05) da IV após o período competitivo (PRE=54,19 ± 4,46 e POS=57,94 ± 5,23). De acordo com os resultados deste estudo, é possível aumentar o desempenho da IV em atletas profissionais de futebol após o período competitivo com 20 semanas de duração.
Keywords: Countermovememt jump; Competitive season; Soccer; Impulsão vertical contra movimento; Período competitivo; Futebol